2022
DOI: 10.1042/bst20220851
|View full text |Cite
|
Sign up to set email alerts
|

Lumenal components of cytoplasmic microtubules

Abstract: The lumen of cytoplasmic microtubules is a poorly explored expanse of intracellular space. Although typically represented in textbooks as a hollow tube, studies over several decades have shown that the microtubule lumen is occupied by a range of morphologically diverse components. These are predominantly globular particles of varying sizes which appear to exist either in isolation, bind to the microtubule wall, or form discontinuous columns that extend through the lumenal space. Actin filaments with morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…In any case, the presence of these structures in HAP1 cell projections highlights the importance of considering intermediates on an assembly/disassembly pathway. This may be particularly important when examining morphologically diverse lumenal material in other cell types that has filamentous character but unknown composition 27 . Structural studies of Class II and Class III filaments are, therefore, a priority.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, the presence of these structures in HAP1 cell projections highlights the importance of considering intermediates on an assembly/disassembly pathway. This may be particularly important when examining morphologically diverse lumenal material in other cell types that has filamentous character but unknown composition 27 . Structural studies of Class II and Class III filaments are, therefore, a priority.…”
Section: Resultsmentioning
confidence: 99%
“…There are now many high-resolution imaging studies examining microtubules in their native environment that have not observed lumenal filaments but that have observed extensive particulate and globular lumenal material, for example, in neurons 31 , 32 and malaria parasites 33 , 34 , as well as others reviewed in ref. 27 . However, filamentous lumenal structures have recently been observed in fibroblasts grown in cell-derived matrices 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This requires dynamic changes of MT networks driven by processes of nucleation, de−/polymerisation, repair, posttranslational modification and cross-linkage, all mediated by MT-binding proteins (‘Eb, X, Sp, 11, 18’ in Figure 1 >a + b/m + n and e/g; some details further below; Conde and Caceres, 2009 ; Hahn et al, 2019 ; Janke and Magiera, 2020 ). MTs were also reported to contain proteins in their lumen which might regulate MT stability; these include actin filaments, MAP 6 and chaperones ( Cuveillier et al, 2020 ; Paul et al, 2020 ; Chakraborty et al, 2022 ; Tsuji and Dodding, 2022 ).…”
Section: Roles and Regulations Of The Cytoskeleton In Axonsmentioning
confidence: 99%
“…In any case, the presence of these structures in HAP1 cell projections highlights the importance of considering intermediates on an assembly/disassembly pathway. This may be particularly important when examining morphologically diverse lumenal material in other cell types that has filamentous character but unknown composition [25]. Structural studies of Class II and Class III filaments are therefore a priority.…”
Section: We Did Not Observe Clear Examples Of Class II and Class Iii ...mentioning
confidence: 99%